2016
DOI: 10.3389/fncel.2016.00043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Injury Induces Brain Endothelial-Derived Microvesicle Release: Implications for Cerebral Vascular Injury during Traumatic Brain Injury

Abstract: It is well established that the endothelium responds to mechanical forces induced by changes in shear stress and strain. However, our understanding of vascular remodeling following traumatic brain injury (TBI) remains incomplete. Recently published studies have revealed that lung and umbilical endothelial cells produce extracellular microvesicles (eMVs), such as microparticles, in response to changes in mechanical forces (blood flow and mechanical injury). Yet, to date, no studies have shown whether brain endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 52 publications
4
67
0
Order By: Relevance
“…Also, lending support are reports by Takahashi et al [40] and Haqqani et al [39] that cultures of human aortic endothelial cells and human BMEC, respectively, release EVs containing junctional proteins. Most recently, Andrews et al [41] described the release from cultured human BMECs of EVs containing the TJ protein occludin, following application of mechanical trauma to these cells, and additionally noted EVs bearing this protein were elevated in blood plasma of mice subject to traumatic brain injury (TBI). Further paralleling our results for CLN-5 + vesicles, these authors observed that occludin + EVs stemming from trauma were of both exosome and microvesicle size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, lending support are reports by Takahashi et al [40] and Haqqani et al [39] that cultures of human aortic endothelial cells and human BMEC, respectively, release EVs containing junctional proteins. Most recently, Andrews et al [41] described the release from cultured human BMECs of EVs containing the TJ protein occludin, following application of mechanical trauma to these cells, and additionally noted EVs bearing this protein were elevated in blood plasma of mice subject to traumatic brain injury (TBI). Further paralleling our results for CLN-5 + vesicles, these authors observed that occludin + EVs stemming from trauma were of both exosome and microvesicle size.…”
Section: Discussionmentioning
confidence: 99%
“…As mechanical trauma to the CNS microvasculature is also associated with endothelial activation, immune reaction, and neuroinflammation [77–79], BMEC release of EVs carrying TJ proteins might be a general phenomenon linked to CNS leukocyte infiltration. Notably, Andrews et al [41] also found the percent of occludin + EVs in the blood of TBI mice to be comparatively minor, e.g., <6% of total EVs, compared to ~1% of CLN-5 + EVs detected in mice with early-stage EAE. The slight discrepancies in the observed percentages could be due to differences in the experimental conditions employed, with TBI possibly being more disruptive to the vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, platelet endothelial cell adhesion molecule-1 (PECAM-1, CD31) is known to produce neuroinflammation and subsequent blood brain barrier disruption, and accumulating evidence suggests that it could be used as a potential marker for neurological disorders (Losy et al, 1999, Zaremba and Losy, 2002, Hwang et al, 2005, Kalinowska and Losy, 2006, Woodfin et al, 2007, Privratsky et al, 2010, Cheung et al, 2015, Andrews et al, 2016). However, it is not known whether withdrawal from chronic ethanol experience regulates PECAM-1 and if the alterations in PECAM-1 correlate with withdrawal induced increases in oligodendroglia and myelinating glia.…”
Section: 0 Introductionmentioning
confidence: 99%
“…That is, MSCs-derived exosomes that carry and transfer their cargo such as miRNAs to parenchymal cells may mediate brain plasticity and improve functional recovery after TBI [204]. Furthermore, another potential application of brain endothelial-derived eMVs could be as biosignatures for monitoring the health of the BBB in CNS conditions associated with trauma and neuroinflammation [239].…”
Section: Extracellular Vesicles and Exosomesmentioning
confidence: 99%